Too Imperfect to Fall Asleep: Perfectionism, Pre-sleep Counterfactual Processing, and Insomnia - Schmidt, Ralph E.; Courvoisier, Delphine S.; Cullati, Stéphane; Kraehenmann, Rainer; Linden, Martial Van der (Frontiers in Psychology, 2018)
Previous research suggests that certain dimensions of perfectionism are associated with insomnia. However, the exact processes whereby perfectionism may influence sleep have as yet remained unexplored. The present study tested the hypothesis that perfectionistic individuals are particularly prone to engage in counterfactual thinking and to experience counterfactual emotions (regret, shame, and guilt) at bedtime, which have been shown to impair sleep. One hundred eighty university students completed questionnaires on perfectionism, counterfactual processing, and insomnia severity. Analyses revealed that three dimensions of perfectionism were significantly related to insomnia severity: Concern over mistakes and doubts about action showed positive correlations, whereas organization showed a negative correlation. Moreover, the frequency of counterfactual thoughts and emotions at bedtime largely mediated the effects of these dimensions of perfectionism on insomnia severity. These findings highlight how personality-related patterns of behavior may translate into affective arousal at bedtime, thereby increasing the risk of insomnia.